Ionizing radiation-induced disruption of Rela-Bclaf1-spliceosome regulatory axis in primary spermatocytes causing spermatogenesis dysfunction - Hongjian Zhou; Zhipeng Xu; Chun Jiang; Qiuyue Wu; Chuanyue Zhang; Zhenyu Liu; Xiaoxue Zhang; Weiwei Li; Yujia Pang; Jing Zhang; Wenju Pan; Min Chen; et al. (Cell Communication and Signaling)
Abstract Introduction Ionizing radiation (IR) poses a significant threat to male fertility by inducing substantial changes in the testis, yet the mechanisms underlying IR-induced spermatogenesis disorders remain poorly understood, necessitating the development of more effective radioprotective agents. Methods We employed Bulk RNA-seq and single-cell RNA-seq (scRNA-seq) on Balb/c mice testes models following IR exposure to assess cellular and transcriptional alterations. Histological examination, sperm concentration and motility analysis, Western blotting (WB), and reverse transcription quantitative PCR (RT-qPCR) were used to evaluate testicular injury. The therapeutic potential of NF-κB agonists was investigated in an IR-induced spermatogenesis disorder model. Results A 6 Gy IR dose induced spermatogenesis disorder and suppressed the spliceosome pathway, predominantly affecting the cell abundance of spermatogonia and primary spermatocytes. Bioinformatics analysis revealed that IR induced splicing disorders in differentiation-related genes, thereby impairing the differentiation ability of primary spermatocytes. Mechanistically, This IR-induced disruption was linked to IR-induced inhibition of NF-κB/Rela and Bclaf1 activity. Notably, NF-κB agonists were found to ameliorate this damage via upregulating Bclaf1 and spliceosome-related genes expression, thereby normalizing splicing patterns and rescuing IR-induced spermatogenesis disorders. Conclusion This study reveals a novel IR-mediated Rela-Bclaf1-spliceosome regulatory axis in primary spermatocytes and propose Rela as a potential drug target for mitigating IR-induced spermatogenesis disorders. This study not only provides new insights for further research into IR-induced damage and spermatogenic disorders caused by other factors, but also offers potential therapeutic strategies for developing radioprotective agents in cancer radiotherapy.